Multi-purpose rainwater harvesting for water resource recovery and the cooling effect. (1st December 2015) - An, Kyoung Jin; Lam, Yun Fat; Hao, Song; Morakinyo, Tobi Eniolu; Furumai, Hiroaki
Abstract: The potential use of rainwater harvesting in conjunction with miscellaneous water supplies and a rooftop garden with rainwater harvesting facility for temperature reduction have been evaluated in this study for Hong Kong. Various water applications such as toilet flushing and areal climate controls have been systematically considered depending on the availability of seawater toilet flushing using the Geographic Information System (GIS). For water supplies, the district Area Precipitation per Demand Ratio (APDR) has been calculated to quantify the rainwater utilization potential of each administrative district in Hong Kong. Districts with freshwater toilet flushing prove to have higher potential for rainwater harvest and utilization compared to the areas with seawater toilet flushing. Furthermore, the effectiveness of using rainwater harvesting for miscellaneous water supplies in Hong Kong and Tokyo has been analyzed and compared; this revives serious consideration of diurnal and seasonal patterns of rainfall in applying such technology. In terms of the cooling effect, the implementation of a rooftop rainwater harvesting garden has been evaluated using the ENVI-met model. Our results show that a temperature drop of 1.3 °C has been observed due to the rainwater layer in the rain garden. This study provides valuable insight into the applicability of the rainwater harvesting for sustainable water management practice in a highly urbanized city. Graphical abstract: Area precipitation-demand ratio (APDR) in Hong Kong and Japan. Highlights: Utilization of rainwater harvesting for water supplies and temperature reduction. Increase of the self-sufficiency of freshwater by 7% and 9% in Hong Kong and Tokyo, respectively. High potential of toilet flushing in the case study elucidated by the high self-sufficiency value. A temperature drop of 1.3 °C by establishing rain garden in the case study. Energy saving in the building due to the cooling effect at the top of the building.